2001
DOI: 10.1136/jcp.54.11.836
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterisation of invasive breast cancer: a comparison of CGH and PCR based multiplex microsatellite analysis

Abstract: Aims-Comparative genomic hybridisation (CGH) is a reliable tool to gain an overview of all unbalanced chromosomal alterations within a tumour. Nevertheless, the high numbers of tumour cells required and the comparatively low resolution are drawbacks of this technique. Polymerase chain reaction (PCR) based multiplex microsatellite analysis represents a semiautomated, highly reproducible method, which requires small amounts of tumour cells. This is a comparative study of CGH and microsatellite analysis. Methods-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 15 publications
0
22
0
1
Order By: Relevance
“…31,53 The percentage of 16q deletion reported varies in studies published in the medical literature according to the sensitivity of the technique used and the distribution of types of breast cancer within the series. For example, Buerger et al 54 found that the overall rate of concordance between LOH and CGH in detection of genomic copy alterations in breast cancer was 61%. In our study, deletion at 16q22.1 was detected in 63% of cases (22/35).…”
Section: C) Telomeric Repeat Binding Factor-2mentioning
confidence: 99%
“…31,53 The percentage of 16q deletion reported varies in studies published in the medical literature according to the sensitivity of the technique used and the distribution of types of breast cancer within the series. For example, Buerger et al 54 found that the overall rate of concordance between LOH and CGH in detection of genomic copy alterations in breast cancer was 61%. In our study, deletion at 16q22.1 was detected in 63% of cases (22/35).…”
Section: C) Telomeric Repeat Binding Factor-2mentioning
confidence: 99%
“…These studies have also shown that deletions of the whole arm of 16q seem to be more frequently found in grade 1 luminal A breast cancers (9 -12), whereas the majority of basal-like and HER-2 cancers (which are usually of high histologic grade) lack this genetic aberration. There is now increasing evidence suggesting that grade 3 and 1 breast cancers are clinically and genetically distinct entities and that progression from grade 1 to 3 breast cancer is an uncommon biological phenomenon (9,10,12). In fact, concurrent presence of grade 1 and 3 areas in the same specimen is seen in <10% of cases (13).…”
Section: Human Cancer Biologymentioning
confidence: 99%
“…[14][15][16][17][18][19][20] The cumulative data have contributed to our understanding of the genomic heterogeneity of breast tumors and work is ongoing to determine how genomics determines both tumor phenotype and prognosis. However, there has been no single platform on which this work has been conducted, and in an era of array CGH, lack of array standardization has impeded direct comparison among groups.…”
Section: Discussionmentioning
confidence: 99%